Tissue-Resident Macrophages in Fungal Infections - Xu, Shengjie; Shinohara, Mari L. (Frontiers in Immunology, 2017)
Invasive fungal infections result in high morbidity and mortality. Host organs targeted by fungal pathogens vary depending on the route of infection and fungal species encountered. Cryptococcus neoformans infects the respiratory tract and disseminates throughout the central nervous system (CNS). Candida albicans infects mucosal tissues and the skin, and systemic Candida infection in rodents has a tropism to the kidney. Aspergillus fumigatus reaches distal areas of the lung once inhaled by the host. Across different tissues in naïve hosts, tissue-resident macrophages are one of the most populous cells of the innate immune system. Although they function to maintain homeostasis in a tissue-specific manner during steady state, tissue-resident macrophages may function as the first line of defense against invading pathogens and may regulate host immune responses. Thus, in any organs, tissue-resident macrophages are uniquely positioned and specifically programmed to function. This article reviews the current understanding of the roles of tissue-resident macrophages during major fungal infections.